2015
DOI: 10.12691/jfnr-3-1-5
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Microfiltration on Particle Size Distribution, Volatile Compounds and Protein Quality of Pasteurized Milk during Shelf Life

Abstract: The effects of microfiltration on particle size, volatiles, protein quality and proximate compositions in pasteurized milk were studied over 7 days at 4°C. Changes in proximate compositions, pH, particle size, amino acids and volatile compounds of microfiltered and pasteurized milk (MPM) and pasteurized milk (PM) were evaluated. The MPM had lower values of proteins and total solids, and possessed higher particle size compared with PM. The D10 and D50 in MPM were individually reduced by 8.3% and 3.1% from day 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 25 publications
(45 reference statements)
1
9
0
Order By: Relevance
“…Similarly, Vegas and Roussis [13] reported an increase in butanoic, hexanoic, octanoic, and decanoic acids in pasteurized milk compared to raw cow milk. Acids identified in this study have previously been found in milk pasteurized by microfiltration and ultrapasteurized milk with dominance of hexanoic and octanoic acids, respectively, [18,29,44] who indicated that pasteurization with microfiltration caused a greater increase in acids than pasteurization only. Although the fat content of commercial UHT milk samples analyzed is standardized to values of ≤3% and <3.5% as UHT whole milk, the values of free fatty acids showed a wide variation from brand to brand, ranging from 25.78 to 87.96%.…”
Section: Vcssupporting
confidence: 60%
See 2 more Smart Citations
“…Similarly, Vegas and Roussis [13] reported an increase in butanoic, hexanoic, octanoic, and decanoic acids in pasteurized milk compared to raw cow milk. Acids identified in this study have previously been found in milk pasteurized by microfiltration and ultrapasteurized milk with dominance of hexanoic and octanoic acids, respectively, [18,29,44] who indicated that pasteurization with microfiltration caused a greater increase in acids than pasteurization only. Although the fat content of commercial UHT milk samples analyzed is standardized to values of ≤3% and <3.5% as UHT whole milk, the values of free fatty acids showed a wide variation from brand to brand, ranging from 25.78 to 87.96%.…”
Section: Vcssupporting
confidence: 60%
“…This could be attributed to the different process technology, quality of initial raw milk and the high storage temperatures since the contents of free fatty acid are increased in UHT milk produced from the raw material with the largest number of psychrotrophic bacteria and stored at the high temperatures [54] and also in milk pasteurized by microfiltration. [18,29,44] Although ethanol was found in all the samples at trace levels, 2-furan methanol, 2-pentanol, and 2-ethyl-1-hexanol were determined in some UHT milk samples as the major alcohols. These alcohols may be formed by the reduction of aldehydes, were previously identified in milk powder.…”
Section: Vcsmentioning
confidence: 96%
See 1 more Smart Citation
“…The volatile compounds were determined in triplicate by GC-MS as described previously. [7] Briefly, samples were extracted from milk using the SPME technique that was performed using an autosampler (GC Sampler 80, Agilent, Santa Clara, CA, USA). A milk sample (10 mL), 2 μL of the internal standard solution (0.1 mg/mL 2,4,6-trimethylpyridine in methanol), and 3.7 g of sodium chloride were placed in an annealed 20-mL brown glass vial with screw cap.…”
Section: Gc-msmentioning
confidence: 99%
“…[3] The flavor properties of cow milk and its products vary depending on cow species, daily diet, environment, age, biological factors, processing, packaging material, and storage conditions. [2,3,[5][6][7] Traditionally, heat treatments, particularly ultra-high temperature (UHT) processing, have been used to eliminate potential pathogens and spoilage organisms in milk. However, they produce thermally derived-off flavor compounds such as aldehydes, methyl ketones, and various sulfur compounds.…”
Section: Introductionmentioning
confidence: 99%